Professional cleaning and risk of asthma - a Danish nationwide register-based study - Camilla Sandal Sejbaek; Esben Meulengracht Flachs; Tanja Korfitsen Carøe; Harald William Meye; Marie Frederiksen; Karen Bo Frydendall; Peder Wolkoff; Per Axel Clausen; Karin Sørig Hougaard; Vivi Schlünssen (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVE: This study aimed to investigate the risk of asthma among professional cleaners in a nationwide population-based study. METHODS: Professional cleaners, aged 16-50 years, were identified according to the yearly assigned administrative job and industrial codes in a register-based, matched cohort study with other manual workers as references (1995-2016). Asthma was defined from national registers based on hospitalization and medication. Associations between recent and cumulative cleaning years and risk of asthma were estimated using Poisson regression, first in a full cohort and then in an inception cohort, among workers aged 16-20 years at the start of follow-up. RESULTS: The risk of asthma was not increased for recent cleaning compared to references [adjusted incidence rate ratio (IRRadj) 1.02 [95% confidence interval (CI) 0.99-1.04]. Similar results were seen for the inception cohort, where cumulative years of cleaning were associated with increased risk of asthma, more prominent for the group with the maximum of six years of cleaning IRRadj 2.53 (95% CI 1.38-4.64). Cumulative years of cleaning were associated with decreased risk of asthma, more pronounced for the maximum of ten compared to one year of cleaning [IRRadj 0.74 (95% CI 0.63-0.88)]. CONCLUSIONS: Asthma risk was increased in the inception cohort for cumulative years of cleaning but decreased in the full cohort. We could not confirm that recent work within cleaning was associated with increased risk of asthma. This may be due to healthy worker bias. Thus, we cannot rule out that long-term professional cleaning may be associated with increased risk of asthma.